Diversidade funcional de comunidades de plantas em gradientes de altitude em ecossistema semiárido brasileiro - Almeida, Gilbevan Ramos de (2018)
Semi-arid ecosystems are marked by climatic seasonality, in which the presence of a dry season imposes on the plant species a severe water stress, limiting many ecosystemic processes. Different functional strategies are used by plants to withstand the adverse conditions of these environments, especially in altitudinal gradients. Variations in functional traits between plants are interpreted as adaptations of species to environmental conditions in response to the acquisition and use of resources necessary for their development. Linking species and changing environmental factors depends on approaches that consider the traits exhibited by species. The main objective of this dissertation was to investigate the structure and the functioning of the shrub-tree communities of the Caatinga under altitude gradients. The characterization of the functional composition and functional diversity metrics aimed to identify the dependence relations, as well as responses, between the species to the structural modification of the communities and of abiotic factors with the altitude. This work was carried out in two mountainous areas in the Brazilian semi - arid with a range of attitudinal variation of 400 m - 690 m. A total of 145 sample units were implanted to sample shrubby tree vegetation, accounting for about one hectare in each study area. For the structural analysis in each of the all living shrubs with DNS (diameter soil at level) ≥ 3 cm and heights ≥ 1 meters were sampled, identified and measured. From the structural data of the shrub-tree species communities of the areas, species of greater abundance of both areas were selected, accounting for 27 species for the functional analyzes. Ten functional traits were measured, including continuous and categorical traits, which reflect strategies related to establishment, persistence and dispersion. The collection, treatment and measurement of functional traits were done according to the standard protocol and specialized literature. The calculations for functional metrics were made for each individual trait reflecting their representativeness in the community by means of community-weighted averages and, subsequently, four indexes of functional diversity (richness, equability, divergence and dispersion) were calculated with those traits correlated. Linear models involving structural and functional variables with altitude were constructed to unravel the responses of the species along the altitude. The results allowed us to conclude: (1) the richness and diversity of species increased with increasing altitude, (2) the species adopted different ecological strategies along the altitude, which reflected in the variation of most of the functional traits analyzed at community level; (3) greater richness, equability and functional dispersion at higher altitudes, indicate a higher degree of niche differentiation, and therefore greater complementarity of resource use between species, and (4) lower altitudinal plant communities dominated by few species lower functional diversity. The mountains studied have greater functional and species diversity and, therefore, are important areas for conservation.